Preface - Kaushik, Shiv K.; Zalik, Richard A. (Communications in Mathematics and Applications, 2012)
"For East is East and West is West, and never the twain shall meet” said the poet, and how wrong he was! East did meet West, again, at ‘International Workshop on Wavelets, Frames and Applications ’ held during December 15-21, 2011, organized by Kirori Mal College, University of Delhi, Delhi. Delegates came from different corners of India, from Iran and Jordan, from Russia and the USA, of different backgrounds and ethnicities, different creeds and beliefs, and they found common ground in their passion for Mathematics. The main purpose of the workshop was to motivate young research scholars in the field of Wavelets, Frames and Applications and to give them a chance to interact with the specialists working in this area. The proceedings consist of fourteen articles and cover a variety of topics of current interest, such as shift-invariant spaces, approximate identities on non-Euclidean manifolds, approximate solutions of operator equations based on frame bounds, wavelet frames, frames in Banach spaces, and multivariate framelets, to name just a few. We express our sincere gratitude to the contributors for submitting their papers and to those who extended their help and cooperation in refereeing the articles of this special issue. The International Workshop on Wavelets, Frames and Applications was jointly sponsored by National Board for Higher Mathematics, Department of Atomic Energy, Government of India (NBHM/Conf. 22/2011/784), Department of Science and Technology (SR/SS/449/11-12), University Grants Commission (F. No. 7-3(47)/2011(Sem/NRCB)), Council of Scientific and Industrial Research (CSIR) (SYM/6285/11-HRD), Shakti Educational and Cultural Society, New Delhi and RGN Publications, Delhi. The editors wish to thank Kirori Mal College, University of Delhi, Delhi for its hospitality and support, and to all those who helped make this workshop such a success. Finally, the editors thank RGN Publications for publishing the proceedings of the workshop in a special issue of the journal "Communications in Mathematics and Applications”.